COVID-19 is a risk factor for retinal vein occlusion in younger patients? - A.G. Shchuko; M.V. Akulenko; T.N. Yur’eva (РМЖ "Клиническая офтальмология")
A.G. Shchuko1,2,3, M.V. Akulenko1, T.N. Yur’eva1,2,3 1Irkutsk Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Irkutsk, Russian Federation 2Irkutsk State Medical Academy of Professional Education — Branch of the Russian Medical Academy of Continuous Professional Education, Irkutsk, Russian Federation 3Irkutsk State Medical University, Irkutsk, Russian Federation Retinal vein occlusions (RVOs) are thought to have more favorable outcomes in patients under-50 due to spontaneous regression. However, 20% develop severe neovascularization. In most cases, the causal link of occlusion remains elusive. Some authors report on clinical presentations typical for RVOs in the COVID-19 infection due to hypercoagulation. Management of younger patients with RVO required a complex diagnostic approach to assess systemic risk factors and obligatory evaluation of baseline retinal ischemia using fluorescein angiography (FA) or optical coherence tomography angiography (OCTA). Clinical criteria of escalating retinal ischemia are decreased central visual acuity, macular edema, increased area of ischemia, and (later) retinal and/or anterior segment neovascularization. We describe a young man with RVO after the COVID-19 infection. The COVID-19 infection had no significant effect on hemostasis parameters in this patient. Meanwhile, the COVID-19 infection cannot be ruled out as an aggravating factor in a patient with a genetic predisposition to (micro)vascular occlusions. Keywords: OCTA, retinal neovascularization, retinal vein occlusion, coagulogram, COVID-19. For citation: Shchuko A.G., Akulenko M.V., Yur’eva T.N. COVID-19 is a risk factor for retinal vein occlusion in younger patients? Russian Journal of Clinical Ophthalmology. 2022;22(1):62–67 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-62-67.